Ordering events in a developing genetic code - Michael Yarus (RNA Biology)
Preexisting partial genetic codes can fuse to evolve towards the complete Standard Genetic Code (SGC). Such code fusion provides a path of ‘least selection’, readily generating precursor codes that resemble the SGC. Consequently, such least selections produce the SGC via minimal, thus rapid, change. Optimal code evolution therefore requires delayed wobble. Early wobble encoding slows code evolution, very specifically diminishing the most likely SGC precursors: near-complete, accurate codes which are the products of code fusions. In contrast: given delayed wobble, the SGC can emerge from a truncation selection/evolutionary radiation based on proficient fused coding.